Tradisi Pangeri pada Masyarakat Kuta Tinggi Kecamatan Badar Kabupaten Aceh Tenggara - Arlita, Novia (YASIN, 2023)
Kuta Tinggi Village, Badar District, Southeast Aceh Regency is a village whose people still maintain and uphold customs and religion highly. Every time there is an event, they still carry out the Customs. Like the Pangeri tradition (plain flour) where this tradition is still carried out at weddings and apostle circumcision. Especially during weddings for the bride, some carry out the Pangeri tradition by violating Islamic law, such as not wearing the headscarf and shaking hands with those who are not mahrams, but it can be underlined that most people are still unfamiliar with such things, for those who understand religion it is impossible not to wearing headscarves etc. so that the writer is interested in researching the views of community leaders and religious scholars on the Pangeri Tradition in terms of the study of religions. The research method used by the author is a qualitative method of the Field Research type with the Phenomenology of Religion approach using symbolic interaction theory. Sources of data generated by the author is from the results of interviews, observation and documentation. The results of the study show that the views of the community and religious scholars towards the Pangeri tradition are well done and there are no harm as long as we do it the right way and do not violate Islamic law.